Vascular Calcification and not Arrhythmia in Idiopathic Atrial Fibrillation Associates with Sex Differences in Diabetic Microvascular Injury miRNA Profiles - Dudink, Elton; Florijn, Barend; Weijs, Bob; Duijs, Jacques; Luermans, Justin; Peeters, Frederique; Schurgers, Leon; Wildberger, Joachim; Schotten, Ulrich; Bijkerk, Roel; Crijns, Harry J.; van Zonneveld, Anton J. (MicroRNA, 2019)
Background: Atrial Fibrillation (AF) in patients without concomitant cardiovascular pathophysiological disease, is called idiopathic Atrial Fibrillation (iAF). Nonetheless, iAF patients have often times subclinical coronary (micro) vascular dysfunction and, particularly in women, a higher prevalence of subsequent cardiovascular comorbidities. Previously, we identified a plasma miRNA association with diabetes and microvascular injury in Diabetic Nephropathy (DN) patients. Therefore, in this study we assessed whether plasma levels of these diabetic, microvascular injury associated miRNAs reflect microvascular integrity in iAF patients, associated with the presence of paroxysmal arrhythmia or instead are determined by concealed coronary artery disease. Methods: Circulating levels of a pre-selected set of diabetic, (micro) vascular injury associated miRNAs, were measured in 59 iAF patients compared to 176 Sinus Rhythm (SR) controls. Furthermore, the presence of coronary artery and aortic calcification in each patient was assessed using Cardiac Computed Tomography Angiography (CCTA). Results: Paroxysmal arrhythmia in iAF patients did not result in significant miRNA expression profile differences in iAF patients compared to SR controls. Nonetheless, coronary artery calcification (CAC) was associated with higher levels of miRNAs-103, -125a-5p, -221 and -223 in men. In women, CAC was associated with higher plasma levels of miRNA-27a and miRNA-126 and correlated with Agatston scores. Within the total population, ascending Aortic Calcification (AsAC) patients displayed increased plasma levels of miRNA-221, while women, in particular, demonstrated a Descending Aorta Calcification (DAC) associated increase in miRNA-212 levels. Conclusions: Diabetic microvascular injury associated miRNAs in iAF are associated with subclinical coronary artery disease in a sex-specific way and confirm the notion that biological sex identifies iAF subgroups that may require dedicated clinical care.
Keywords: sex-differences